ZAKAT WAKALAH DISTRIBUTION EFFECTIVENESS: INSIGHTS FROM ACCOUNTABILITY AND SOCIAL PERFORMANCE MEASUREMENT IN THE NON-PROFIT SECTOR - Zaini, Naimah; Arshad, Roshayani; Muda, Ruhaini; Omar, Nor Bahiyah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Zakat has long been recognised as an essential instrument for socio-economic development in Muslim societies. In Malaysia, the practice of zakat wakalah, where zakat payers are authorised to distribute a portion of their zakat directly, has become an important mechanism to support social initiatives. Despite this, zakat institutions continue to face persistent criticisms related to transparency, efficiency, and accountability. While non-profit organisations have adopted performance measurement frameworks to evaluate their social outcomes and impacts, zakat institutions have yet to establish a structured approach to assess and communicate their social performance. This study addresses this gap by critically reviewing the literature on accountability, performance measurement, and Islamic social finance, with the aim of developing a conceptual framework for measuring the social performance of zakat wakalah distribution. The paper contributes theoretically by extending the application of performance measurement frameworks into the Islamic social finance context, and practically by providing zakat institutions with a foundation to enhance accountability, transparency, and stakeholder trust.